Methods for assessment of patient adherence to removable orthoses used after surgery or trauma to the appendicular skeleton: a systematic review - Gareth Davies; Daniel Yeomans; Zoe Tolkien; Irene A. Kreis; Shelley Potter; Matthew D. Gardiner; Abhilash Jain; James Henderson; Jane M. Blazeby (Trials, 2020)
Abstract Background Patient adherence to treatment is a key determinant of outcome for healthcare interventions. Whilst non-adherence has been well evidenced in settings such as drug therapy, information regarding patient adherence to orthoses, particularly in the acute setting, is lacking. The aim of this systematic review was to identify, summarise, and critically appraise reported methods for assessing adherence to removable orthoses in adults following acute injury or surgery. Methods Comprehensive searches of the Ovid versions of MEDLINE, Embase, AMED, CINAHL, Central, the Cochrane Database of Systematic Reviews, and SPORTDiscus identified complete papers published in English between 1990 and September 2018 reporting measurement of adherence to orthoses in adults following surgery or trauma to the appendicular skeleton. Only primary studies with reference to adherence in the title/abstract were included to maintain the focus of the review. Data extraction included study design, sample size, study population, orthosis studied, and instructions for use. Details of methods for assessing adherence were extracted, including instrument/method used, frequency of completion, number of items (if applicable), and score (if any) used to evaluate adherence overall. Validity and reliability of identified methods were assessed together with any conclusions drawn between adherence and outcomes in the study. Results Seventeen papers (5 randomised trials, 10 cohort studies, and 2 case series) were included covering upper (n = 13) and lower (n = 4) limb conditions. A variety of methods for assessing adherence were identified, including questionnaires (n = 10) with single (n = 3) or multiple items (n = 7), home diaries (n = 4), and discussions with the patient (n = 3). There was no consistency in the target behaviour assessed or in the timing or frequency of assessment or the scoring systems used. None of the measures was validated for use in the target population. Conclusions Measurement and reporting of adherence to orthosis use is currently inconsistent. Further research is required to develop a measurement tool that provides a rigorous and reproducible assessment of adherence in this acute population. Trial registration PROSPERO: CRD42016048462 . Registered on 17/10/2016.